Peran Konektivitas Dewan Independen Dalam Mengurangi Risiko Bank: Implikasi Terhadap Stabilitas Keuangan Dan Kebijakan Moneter Bank Sentral - Agus Revalen Simbolon; Aldi Desandro Sinaga; Arion Silver Aritonang; Eti (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Banking stability is crucial for the health of the financial system, as high bank risk can disrupt overall economic stability. This study aims to analyze the role of independent directors’ connectedness in reducing bank risk and its implications for financial stability and central bank monetary policy. This study employs a quantitative method with a panel data approach to analyze the effect of independent directors’ connectedness on bank risk in six ASEAN countries (Indonesia, Malaysia, Singapore, Thailand, the Philippines, and Vietnam) during the 2018–2022 period. The connectedness of the board is measured through the interlinkages among board members, while bank risk is measured using the z-score. The results indicate that the higher the level of independent directors’ connectedness which reflects greater network capacity, access to information, and strategic coordination the lower the risk faced by banks.. Keywords: Independent Directors’ Connectedness, Bank Risk, Financial Stability, Monetary Policy, Bank Governance Abstrak Stabilitas perbankan sangat penting bagi kesehatan sistem keuangan, dan risiko bank yang tinggi dapat mengganggu kestabilan ekonomi. Penelitian ini bertujuan untuk menganalisis peran konektivitas dewan independen dalam mengurangi risiko bank dan implikasinya terhadap stabilitas keuangan serta kebijakan moneter bank sentral. Penelitian ini menggunakan metode kuantitatif dengan pendekatan panel data untuk menganalisis pengaruh konektivitas dewan independen terhadap risiko bank di enam negara ASEAN (Indonesia, Malaysia, Singapura, Thailand, Filipina, Vietnam) selama periode 2018–2022. Konektivitas dewan diukur melalui keterhubungan anggota dewan, sementara risiko bank diukur dengan z-score. Hasil penelitian menunjukkan semakin tinggi tingkat konektivitas dewan independen yang mencerminkan kapasitas jaringan, akses informasi, dan koordinasi strategis yang lebih baik maka semakin kecil risiko yang dihadapi oleh bank. Kata Kunci : Konektivitas Dewan Independen, Risiko Bank, Stabilitas Keuangan, Kebijakan Moneter, Tata Kelola Bank